Acclimation and adaptation of invasive seaweeds - a case study with the brown alga Sargassum muticum - Serebryakova, Alexandra (2017)
Non-indigenous seaweeds impact natural communities worldwide, affecting biodiversity, ecosystem functioning, and ecosystem services, resulting in significant economic and social consequences. Among major impacts are the displacement of native species, a threat to endangered species, and effects on ecological and evolutionary processes within the invaded communities. While critical to predict the fate of introduced species, understanding the mechanisms of acclimation and adaptation following introduction represents a great challenge in seaweeds. In this thesis, we investigated some acclimation processes, with an emphasis on the role of associated microbiota, and examined their effects with Sargassum muticum as a model species. This brown seaweed native to Asia, is an emblematic invader among seaweeds, with a distribution now ranging from Mexico to Alaska in America and from Morocco to Norway in Europe. We first reviewed the competitive advantages and traits that may contribute to its invasiveness. In addition, we provided an overview of putative underlying mechanisms of acclimation and adaptation and highlighted their role in seaweed invasions. We then examined the effects of ocean acidification on the microbiome of S. muticum and revealed that it does not have significant effects on the seaweed-associated microbiota despite certain changes in the microbial community. We further investigated the seasonal changes in the seaweed-associated microbiota and revealed significant differences between seasons and geographic locations. Finally, we applied ecological niche modelling, but innovatively accounting for phenology, to project the distribution of S. muticum under two future climate change scenarios. According to our projections, by 2100 the distribution of S. muticum is expected to shift northwards along its European, North American and Asian distributions with a partial retreat from the currently occupied areas. As algas não indígenas afetam comunidades naturais em todo o mundo, afetando a biodiversidade, o ...